Crustacean chitin nanomaterial as reinforcement for bio-based polymer - Maskur, Miftahul Hidayat; Wan Nawawi, Wan Mohd Fazli; Ali, Fathilah; Al-Khatib, Ma'an Fahmi Rashid (Taylor and Francis Ltd., 2020)
In this study, chitin nanofibers with an average diameter of 80–100 nm were extracted from crab shell and used to reinforce bio-based polymer, polylactic acid (PLA). Solvent-casting and hot-compression moulding were used to fabricate chitin/PLA nanocomposite. Chitin nanofibers were first dispersed in PLA/ chloroform mixture before the solvent was left to evaporate naturally, leaving behind chitin/PLA thin film composite. Thicker specimen of composite was produced by filling the dogbone mould cavities with chloroform-free chitin/PLA film followed by compression moulding at 190°C and 25 bar. Tensile strength tests were performed to evaluate the mechanical properties of the nanocomposite at different chitin concentration loading. Increase in chitin nanofiber content up to 5 wt.% effectively improves the Young’s modulus (E) and tensile strength (σ) of the resulting nanocomposite, of which the highest improvement was found at 5% chitin loading (E = 1.3 GPa, σ = 24 MPa). This account for 13% Young’s modulus and 275% tensile strength improvement compared to neat PLA specimen (E = 1.15 GPa, σ = 6.4 MPa). Further addition of chitin nanofiber decreases the tensile strength performance of the nanocomposite because of chitin-chitin agglomeration, which leads to poor dispersion of the nanofibers within the PLA matrix